DIMENSI PROFIL PELAJAR PANCASILA DALAM KUMPULAN RUPAMA (CERITA RAKYAT MAKASSAR) KARYA ZAINUDDIN HAKIM - Khatima, Khusnul; Hasriani; Nojeng, Asis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the importance of strengthening national character values through local wisdom, particularly in the context of implementing the Pancasila Student Profile. This study aims to describe the dimensions of the Pancasila Student Profile present in the Rupama (Makassar Folk Stories) collection by Zainuddin Hakim and analyze the meanings contained within. Using a descriptive qualitative method and content analysis, the research data were obtained through documentation techniques applied to the rupama texts, which were analyzed based on the six dimensions of the pancasila student profile. The results indicate that all five stories comprehensively encompass the six value dimensions, with the highest frequency found in the dimension of faith, piety, and noble character. These values are manifested through dialogue, actions, and character traits, reflecting Makassar local wisdom related to spirituality, solidarity, independence, critical reasoning, and creativity. The study concludes that Rupama serves as a rich and authentic source of local wisdom, making it an effective medium for character education to internalize the values of the Pancasila Student Profile within the educational sphere.